MOLD DIVERSITY OF WREATHED HORNBILL (Rhyticeros undulatus) NEST IN MOUNT UNGARAN - Margareta Rahayuningsih; Yanuar Revandi; Siti Harnina Bintari (SEAMEO BIOTROP, 2022)
Wreathed Hornbill (Rhyticeros undulates) is known to build nests in three cavities where they managed to live and breed. This edifice is predicted to contain various molds needed to maintain micro-environmental steadiness. This study was aimed to identify molds diversity in the Wreathed Hornbill’s nest, using samples collected from empty structure with no bird activity. The samples were obtained from the Kalisidi and Nglimut observation stations on two occasions, i.e., in 2016 and 2017. Furthermore, the samples comprised cover soil, wood and inner material, which were collected aseptically and placed in sterile Ziplock plastic bags. These samples were then diluted in sterilized distilled water to attain 10-3 mg/ mL, and subsequently inoculated on Potato Dextrose Agar (PDA), Malt Extract Agar (MEA) and Czapek Dox Agar (CDA). The inoculants were incubated at 37 °C, followed by the observation of mold colony after the 11th day. The results identified seven and nine species of molds in the Kalisidi and Nglimut observation stations, respectively. The most abundant species was Penicillium sp. which was found in composted nest materials for the whole observation periods.